2020
DOI: 10.1590/1981-22562020023.200254
|View full text |Cite
|
Sign up to set email alerts
|

Estado nutricional de idosos com doença de Parkinson e seus fatores associados: uma revisão integrativa

Abstract: Resumo Objetivo Identificar os fatores associados ao Estado Nutricional de idosos com doença de Parkinson (DP) por meio de uma revisão integrativa da literatura. Método Foram utilizadas as bases de dados LILACS, MEDLINE, BDENF, Scielo e Pubmed, sem filtros para ano de publicação e desenho do estudo. Foram incluídos os estudos disponibilizados em português, inglês ou espanhol com população idosa (idade ≥60 anos). Foram excluídos estudos que não tratavam da temática, publicações não disponíveis na íntegra e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With regard to nutritional status, PD patients usually tend to be underweight or malnourished, which may be associated with increased energy expenditure caused by the progression of motor symptoms, associated with gastrointestinal symptoms and anorexia arising from the side effects of PD medications, modifying the state patient’s nutritional status [ 6 ]. Nevertheless, in the present study, we observed a different pattern in the studied population, with a higher presentation of overweight and eutrophy, corroborating previous studies [ 5 , 22 , 23 ] that obtained similar data in their analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to nutritional status, PD patients usually tend to be underweight or malnourished, which may be associated with increased energy expenditure caused by the progression of motor symptoms, associated with gastrointestinal symptoms and anorexia arising from the side effects of PD medications, modifying the state patient’s nutritional status [ 6 ]. Nevertheless, in the present study, we observed a different pattern in the studied population, with a higher presentation of overweight and eutrophy, corroborating previous studies [ 5 , 22 , 23 ] that obtained similar data in their analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The bivariate correlation analysis showed that the lower the BMI, the more affected the cognition and the lower the social support. Thus, weight loss in PD has negative clinical and prognostic consequences, which increase the risk of morbidity and mortality [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation